STRATEGIC ORIENTATION: PERSPECTIVE OF DIGITAL LEADERSHIP AND INNOVATION - Wahyudi Wahyudi; Jefri Heridiansyah; Marlina Kusumawati; Sri Wiranti Setiyanti; Ariyani Indriastuti (Institut Pendidikan Tapanuli Selatan, 2026)
Recent research on leadership underscores digital leadership has a role to play in encouraging innovation within MSMEs. However, a gap persists in the previous research the presence and influence of digital leadership. To address this, our study integrates the resource-based approach and social information processing theory for explore how digital entrepreneurial orientation shapes the relationship between digital leadership and exploratory innovation. Through phased data collection from 200 employees and 20 leaders, our results indicate that (a) digital leadership positively influences exploratory innovation, and (b) digital entrepreneurial orientation serves as a mediator in this relationship. This research not only advances the field of organizational digitalization but also deepens the understanding of how digital leadership connects to exploratory innovation. The findings offer significant theoretical contributions to the field of leadership studies and practical recommendations for industry practitioners.